Some Thoughts Regarding Generation Z’s Social Characteristics and Their Likely Effects - Kárpáti, László (Filológia.hu, 2024)
Parents of the current generation are likely to have difficult times shortly, as it becomes more and more demanding and tiresome to safeguard their children’s complete well-being against the outside world. They also face the new challenge of actually cooperating and cohabiting with the ones they swore to protect from any harm. As a result of their children spending an ever-growing number of time stuck to the screens of their smart devices and wasting long hours on the omnipresent internet, there is a high risk to be accounted for here, particularly in the life of teenagers. The present paper aims to shed light on the many negative aspects of using smart devices in our everyday life, particularly in the life of younger children and teenagers. Beyond revealing these effects, it also seeks to offer feasible and working solutions to the above-mentioned issues to compensate for the possible negative influences that are to be discussed.